Carbon nanotube-mediated delivery of budesonide to macrophages. Issue 58 (1st June 2016) - Foillard, Stéphanie; Russier, Julie; Seifert, Cécile; Dumortier, Hélène; Doris, Eric
Abstract : A carbon nanotube-based carrier was developed for the delivery of anti-inflammatory budesonide to intracellular compartments of macrophages. Abstract : Carbon nanotubes were functionalized with budesonide, a potent anti-inflammatory drug, and investigated for interactions with macrophages. Pristine carbon nanotubes were first shortened to make them compatible with cellular dimensions before budesonide was non-covalently appended to their surface via a specifically designed amphiphilic molecule. The resulting nanohybrids were evaluated in regards to their internalisation into macrophages and ability to inhibit pro-inflammatory cytokine secretion. In vitro experiments showed that the budesonide delivery system is readily captured by phagocytic cells and has a deep anti-inflammatory effect as it strongly inhibits IL-6 production.